Increased Expression of Cyclin D1, Cyclin E and p21(Cip1) Associated with Decreased Expression of p27(Kip1) in Chemically Induced Rat Mammary Carcinogenesis - Jang, Tae Jung (Jpn J Cancer Res, 2000)
We induced rat mammary tumors in 7‐week‐old female Sprague‐Dawley rats by intragastric administration of 7,12‐dimethylbenz(a)anthracene (DMBA), and analyzed by immunohistochemistry the expression of cyclin D1, cyclin E, p21(Cip1), and p27(Kip1) in carcinomas, atypical tumors, and benign tumors as well as normal mammary glands from the control group. Proliferation status was assessed by immunohistochemistry using bromodeoxyuridine (BrdU). A sequential increase in cyclin D1‐, cyclin E‐, and p21(Cip1)‐positive epithelial cells was observed from normal mammary glands, to atypical tumors, to carcinomas. In contrast, carcinomas showed a significantly lower number of epithelial cells immunoreactive to p27(Kip1) when compared with atypical tumors, benign tumors and normal mammary glands. The immunoreactivities of BrdU, cyclin D1, cyclin E, and p21(Cip1) were positively correlated, whereas that of p27(Kip1) appeared inversely correlated to those of the others. Reverse transcriptase‐polymerase chain reaction (RT‐PCR) and western blot analysis were also performed to determine the mRNA and protein levels of cyclins and cyclin‐dependent kinase inhibitors in tumors and normal mammary glands. The protein levels for cyclin D1, cyclin E and p21(Cip1) in carcinomas and atypical tumors were significantly higher than those in benign tumors, while normal mammary glands showed negligible expression. On RT‐PCR, tumors showed higher mRNA levels of cyclin D1 and cyclin E than those of normal mammary glands. Our results suggest that rat mammary carcinogenesis involves increased expression of cyclin D1, cyclin E, and p21(Cip1), associated with decreased expression of p27(Kip1)